Legal Protection for the Sale and Purchase of Uncertified Land in Paser Regency, East Kalimantan - Renalda, Audrina; Fajar Riyanto, Taufan (Jurnal Konstatering, 2025)
This research is based on the fact that many people in Paser Regency still conduct land sales and purchases without certificates based solely on trust and simple receipts, thus creating legal uncertainty and potential ownership disputes. The purpose of this research is to understand the process of buying and selling uncertified land, the obstacles encountered, and the forms of legal protection provided to the parties. This research uses an empirical juridical method with a descriptive analytical approach, which combines secondary data in the form of laws and legal theories with primary data from field interviews. The results show that the practice of buying and selling uncertified land in Paser Regency is still carried out underhand without a PPAT deed and does not go through the land registration process as stipulated in Government Regulation Number 24 of 1997. The main obstacles include a lack of public legal awareness, the perceived high cost of certification, and weak village administrative oversight. Legal protection efforts that can be provided include preventive protection through counseling and mandatory land registration, as well as repressive protection through dispute resolution in court. This research emphasizes the need to increase public legal awareness and the active role of local governments and PPATs in ensuring legal certainty for uncertified land transactions.